Photosynthetic capacity, nutrient status, and growth of maize (Zea mays L.) upon MgSO4 leaf-application - Jezek, Mareike; Geilfus, Christoph-Martin; Bayer, Anne; Mühling, Karl-Hermann (Frontiers in Plant Science, 2015)
The major plant nutrient magnesium is involved in numerous physiological processes and its deficiency can severely reduce the yield and quality of crops. Since Mg availability in soil and uptake into the plant is often limited by unfavorable soil or climatic conditions, application of Mg onto leaves, the site with highest physiological Mg demand, might be a reasonable alternative fertilization strategy. This study aimed to investigate, if MgSO4 leaf-application in practically relevant amounts can efficiently alleviate the effects of Mg starvation in maize, namely reduced photosynthesis capacity, disturbed ion homeostasis and growth depression. Results clearly demonstrated that Mg deficiency could be mitigated by MgSO4 leaf-application as efficiently as by resupply of MgSO4 via the roots in vegetative maize plants. Significant increases in SPAD values and net rate of CO2-assimilation as well as enhanced shoot biomass have been achieved. Ion analysis furthermore revealed an improvement of the nutrient status of Mg-deficient plants with regard to [Mg], [K] and [Mn] in distinct organs, thereby reducing the risk of Mn-toxicity at the rootside, which often occurs together with Mg deficiency on acid soils. In conclusion, foliar fertilization with Mg proved to be an efficient strategy to adequately supply maize plants with magnesium and might hence be of practical relevance to correct nutrient deficiencies during the growing season.